Looking beyond the smokescreen: DPEP and primary education in India - Krishna Kumar; Saxena, Sadhna; Priyam, Manisha (2001)
The system of primary education in India has yet to be analysed critically - a critique that would seek to probe the linkages between education and social change. This study seeks to initiate that process by looking at the District Primary Education Programme (DPEP) that was subscribed to by most World Bank borrowers, including India, as a social safety net against the social and economic turmoil that followed any structural adjustment processes. In India, the reach of DPEP extended to 240 districts across 16 states, within the first six years of its existence. Despite this, surveys showed a decline in growth at the primary enrolment stage in most Indian states. More disturbing was the increasing presence of the `para teacher' and the consequent labelling of the full-time teacher as an impediment to the system's further development. - Reproduced
Keywords: Education - India; Primary education - India; Primary education